2020
DOI: 10.1002/hbm.24964
|View full text |Cite
|
Sign up to set email alerts
|

Impact of b‐value on estimates of apparent fibre density

Abstract: Recent advances in diffusion magnetic resonance imaging (dMRI) analysis techniques have improved our understanding of fibre‐specific variations in white matter microstructure. Increasingly, studies are adopting multi‐shell dMRI acquisitions to improve the robustness of dMRI‐based inferences. However, the impact of b‐value choice on the estimation of dMRI measures such as apparent fibre density (AFD) derived from spherical deconvolution is not known. Here, we investigate the impact of b‐value sampling scheme on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 65 publications
(87 reference statements)
7
56
0
Order By: Relevance
“…Finally, using SS3T-CSD, the resulting WM FOD is then also not weighted by the signal from lower b-value(s), and consequently the resulting apparent fibre density is less biased by extra-axonal signal and more specifically sensitised to intra-axonal volume. The latter is consistent with recent findings by Genc et al, (2020) , where use of higher b-values was found to result in more accurate estimates of WM fibre density using simulated data, and corroborated by their in vivo studies.…”
Section: Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…Finally, using SS3T-CSD, the resulting WM FOD is then also not weighted by the signal from lower b-value(s), and consequently the resulting apparent fibre density is less biased by extra-axonal signal and more specifically sensitised to intra-axonal volume. The latter is consistent with recent findings by Genc et al, (2020) , where use of higher b-values was found to result in more accurate estimates of WM fibre density using simulated data, and corroborated by their in vivo studies.…”
Section: Methodssupporting
confidence: 92%
“…This issue can be overcome by modelling GM and CSF signal fractions, for example by using multi-shell multi-tissue CSD ( Jeurissen et al, 2014 ). However, this requires multi-shell data, typically implying the additional use of low b-values, which introduces some amount of extra-axonal signal ( Genc et al, 2020 ). Alternatively, a recently introduced variant of the CSD method, called single-shell 3-tissue CSD (SS3T-CSD) ( Dhollander and Connelly, 2016a , Dhollander et al, 2016 ), is able to additionally estimate the GM and CSF compartments using single-shell diffusion data alone.…”
Section: Introductionmentioning
confidence: 99%
“…After the pre-processing, for each subject a whole-brain mask was defined and a FOD was computed from the highest b-value only (b = 2000 s/mm 2 ) using the Dhollander method ( Dhollander et al, 2016 ). We chose to select only this b-value to avoid any potential extra-axonal signal contribution ( Genc et al, 2020 ), as previously done in other studies ( Dimond et al, 2020 ). The Dhollander method is designed to rely on multi-tissue CSD even in absence of multi-shell data ( Dhollander et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Fixel-based analysis can distinguish between different fiber bundles within a voxel and estimate FD for each fiber bundle separately (FD1 and FD2). For a complete description and interpretation of these measures we refer to the following reviews of DTI analysis (Beaulieu, 2002;Beaulieu, 2014;Song et al, 2002;Zatorre et al, 2012) and fixel based analysis (Genc et al, 2020;Raffelt et al, 2017) It is important to note that fixel-based analysis was mainly created to study the human or mammalian brain. The mammalian cortex has a laminar organization with large white matter tracts interconnecting both hemispheres through the corpus callosum, whereas the avian telencephalon has a nuclear organization with distinct white matter tracts organized in lamina (Jarvis et al, 2005).…”
Section: Population-based Tractogram Of the Starling Brain Using Fixementioning
confidence: 99%